Improving research and learning in higher education in Portugal: Digital resources, e-books, and a discovery system as enabling factors for students - Sanches, Tatiana (2016)
This article describes a library’s implementation of digital resources for research, teaching, and learning at higher education institution in Portugal. A school specializing in education and teacher education established strategic performance areas related to digital resources for the fulfillment of its mission, which included some functions of the academic library. The library implemented a discovery system and the school invested in a wider range of resources, including e-books, both acquired and institutionally published. The library’s training programs were also revised to promote the new system and electronic resources. This case study describes how an academic library in Portugal responded to institutional needs, illustrating how libraries everywhere must connect to the larger vision and demonstrate value through technologies, integrating digital and print resources to provide access built around users' needs.